Asymptotic resource consumption in multicast reservation styles. - Mitzel, Danny J. (Computer communication review.)
The goal of network design is to meet the needs of resident applications in an efficient manner. Adding real-time service and point-to-multipoint multicast routing to the Internet's traditional point-to-point best effort service model will greatly increase the Internet's efficiency in handling point-to-multipoint real-time applications. Recently, the RSVP resource reservation protocol has introduced the concept of ?reservation styles?, which control how reservations are aggregated in multipoint-to-multipoint real-time applications. In this paper, which is an extension of [9], we analytically evaluate the efficiency gains offered by this new paradigm on three simple network topologies: linear, m-tree, and star. We compare the resource utilization of more traditional reservation approaches to the RSVP reservation styles in the asymptotic limit of large multipoint applications. We find that in several cases the efficiency improvements scale linearly in the number of hosts.